Transmedia Narrative as pedagogical support for disciplinary training of students in Higher Education - Ribero Salazar, Fabio (2019)
The paper is the result of research, carried out within the environ- ment of higher education in the city of Bogotá, through the application and development of Transmedia strategies, as a tool for construction, response and appropriation of knowledge within the academic environment. There- fore, the processes developed throughout the research are presented and demonstrates how transmedia can be a useful tool in the pedagogical work of teachers. This study is supported by a theoretical analysis that from the field of educommunication, shows the close relationship that exists between the media, pedagogy and communication and how they relate to ICTs and technological advances.